Analisis Bantuan Sosial, Pendidikan dan Kesehatan di Provinsi Sumatera Barat - Septina Septina; Yeniwati Yeniwati (Universitas Negeri Padang, 2023)
Poverty is a complex and multidimensional problem so that it becomes a development priority. This study aims to analyze: (1) the effect of prosperous rice (Rastra) on poverty. (2) the effect of the prosperous family program (PKH) on poverty. (3) the effect of education on poverty. (4) the effect of health on poverty in West Sumatra Province. This research is a descriptive study using data from the National Socioeconomic Survey (SUSENAS) conducted by the Central Bureau of Statistics (BPS) in 2017. The population for this study was all households in West Sumatra Province, totaling 2,511 people. This study was analyzed using ordinary least squares (OLS) regression analysis using the STATA MP 14 program. Based on the results of the study it can be concluded that (1) Rastra significantly influences poverty. (2) education significantly affects poverty. (3) health significantly affects poverty. (4) PKH does not statistically significantly affect poverty.